IFN-γ- and IL-17-producing CD8+ T (Tc17-1) cells in combination with poly-ICLC and peptide vaccine exhibit antiglioma activity - Takayuki Ohkuri; Akemi Kosaka; Hideho Okada; Maki Ikeura (Journal for ImmunoTherapy of Cancer)
Background While adoptive transfer of T-cells has been a major medical breakthrough for patients with B cell malignancies, the development of safe and effective T-cell-based immunotherapy for central nervous system (CNS) tumors, such as glioblastoma (GBM), still needs to overcome multiple challenges, including effective homing and persistence of T-cells. Based on previous observations that interleukin (IL)-17-producing T-cells can traffic to the CNS in autoimmune conditions, we evaluated CD8+ T-cells that produce IL-17 and interferon-γ (IFN-γ) (Tc17-1) cells in a preclinical GBM model.Methods We differentiated Pmel-1 CD8+ T-cells into Tc17-1 cells and compared their phenotypic and functional characteristics with those of IFN-γ-producing CD8+ T (Tc1) and IL-17-producing CD8+ T (Tc17) cells. We also evaluated the therapeutic efficacy, persistence, and tumor-homing of Tc17-1 cells in comparison to Tc1 cells using a mouse GL261 glioma model.Results In vitro, Tc17-1 cells demonstrated profiles of both Tc1 and Tc17 cells, including production of both IFN-γ and IL-17, although Tc17-1 cells demonstrated lesser degrees of antigen-specific cytotoxic activity compared with Tc1 cells. In mice-bearing intracranial GL261-Quad tumor and treated with temozolomide, Tc1 cells, but not Tc17-1, showed a significant prolongation of survival. However, when the T-cell transfer was combined with poly-ICLC and Pmel-1 peptide vaccine, both Tc1 and Tc17-1 cells exhibited significantly prolonged survival associated with upregulation of very late activation antigen−4 on Tc17-1 cells in vivo. Glioma cells that recurred following the therapy lost the susceptibility to Pmel-1-derived cytotoxic T-cells, indicating that immuno-editing was a mechanism of the acquired resistance.Conclusions Tc17-1 cells were equally effective as Tc1 cells when combined with poly-ICLC and peptide vaccine treatment.